Legal analogy as an alternative to the deductive model of legal reasoning - Koszowski, Maciej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
This article demonstrates the inadequacy of legal deduction as a method that guarantees the certainty and predictability of law and its outcomes in concrete instances. Inter alia, the Author brings our attention to the far smaller role that the deductive pattern of inference plays in legal thought than one may suppose, since it is rather only a schematic illustration of the decisions that were previously made by recourse to the mental operations of a non-logical nature. In return, he proffers legal analogy as an alternative, by which he understands a mode of thinking which helps the reasoner to take into account a mass of different factors that are traditionally deemed to be relevant for legal thought and decision-making.